Evidence from MESSENGER for sulfur‐ and carbon‐driven explosive volcanism on Mercury. Issue 8 (21st April 2016) - Weider, Shoshana Z.; Nittler, Larry R.; Murchie, Scott L.; Peplowski, Patrick N.; McCoy, Timothy J.; Kerber, Laura; Klimczak, Christian; Ernst, Carolyn M.; Goudge, Timothy A.; Starr, Richard D.; Izenberg, Noam R.; Klima, Rachel L.; et al.
Abstract: Targeted MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) X‐Ray Spectrometer measurements of Mercury's largest identified pyroclastic deposit are combined with neutron and reflectance spectroscopy data to constrain the composition of volatiles involved in the eruption that emplaced the pyroclastic material. The deposit, northeast of the Rachmaninoff basin, is depleted in S (relative to Ca and Si) and C, compared with the rest of Mercury's surface. Spectral reflectance measurements of the deposit indicate relatively high overall reflectance and an oxygen‐metal charge transfer (OMCT) absorption band at ultraviolet wavelengths. These results are consistent with oxidation of graphite and sulfides during magma ascent, via reaction with oxides in the magma or assimilated country rock, and the formation of S‐ and C‐bearing volatile species. Consumption of graphite during oxidation could account for the elevated reflectance of the pyroclastic material, and the strength of the OMCT band is consistent with 0.03–0.1 wt % FeO in the deposit. Key Points: MESSENGER data constrain the composition of volatiles involved in the emplacement of Mercury's largest known pyroclastic deposit The NE Rachmaninoff pyroclastic deposit is depleted in S and C compared with the rest of Mercury's surface Results are consistent with oxidation of C and sulfides during magma ascent and the formation of S‐ and C‐bearing volatile species